PERAN PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK SIKAP KRITIS DAN TOLERAN UMAT KRISTEN TERHADAP KONFLIK PEMBANGUNAN RUMAH IBADAH BERDASARKAN ROMA 13:1-2 - Sitorus, Johnson; Waruwu, Anwar Three Millenium (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
SETARA Institute regularly releases data on various cases of violations of religious freedom that have occurred in Indonesia. Data shows that rejection of the construction and closure of houses of worship occurred in several regions, such as East Java, West Java, Central Java, Aceh and several other regions. These cases show that intolerance is still high in Indonesia. Therefore, this study aims to analyze the role of Christian Religious Education (PAK) in developing critical, tolerant, and just attitudes by referring to the results of theological interpretations of Romans 13:1–2. This descriptive qualitative research uses a literature study approach, complemented by a theological approach to explore contextual meaning. Findings based on analysis of the text Romans 13:1-2 show that obedience to the government is a form of obedience to God, without ignoring the principles of justice, love and religious freedom. The research findings illustrate that PAK has a strategic role in equipping Christians peoples to become agents of peace, capable of responding wisely to socio-political conflicts, and balancing obedience to authority with efforts to fight for religious rights. PAK also contributes to the formation of tolerant Christian communities, a harmonious pluralistic society, and improved interfaith relations. Thus, PAK not only shapes individual character but also supports the peaceful creation of social justice and religious freedom